Effects of in ovo feeding of N-acetyl-L-glutamate on early intestinal development and growth performance in broiler chickens - Wang, Jiguang (Poult Sci, 2020)
The present study determined the effects of in ovo feeding (IOF) of N-acetyl-L-glutamate (NAG) on early intestinal development and growth performance of broilers. A total of 702 fertile broiler eggs were randomly divided into 3 treatments: 1) non-punctured control group, 2) saline-injected control group, and 3) NAG solution–injected group (1.5 mg/egg). At 17.5 D of incubation, 300 μL of each solution was injected into each egg of injected groups. Results indicated that the hatchability and healthy chicken rate were not affected by NAG injection (P > 0.05). Chicks from NAG solution–injected group had significantly decreased average daily feed intake and feed conversion ratio during 1–14 D than those in the non-punctured control group (P < 0.05). Compared with the non-punctured control group, IOF of NAG significantly increased the density of goblet cells in jejunum at hatch, duodenum at 7 D, and ileum at 14 D; decreased crypt depth in jejunum at hatch; and increased villus height in duodenum and jejunum and villus height:crypt depth ratio in duodenum at 7 D (P < 0.05). The intestinal mRNA expression of Na(+)-dependent neutral amino acid transporter, peptide transporter, and excitatory amino acid transporter 3 did not differ between groups at 7 or 14 D. However, the mRNA expression level of rBAT in jejunum significantly increased in the NAG solution–injected group than in the non-punctured control group at 7 D (P < 0.05). In conclusion, IOF of NAG (1.5 mg/egg) accelerated the early intestinal development by enhancing intestinal immune and absorption function, thereby positively affecting the feed efficiency for the first 2 wk post-hatch.